PENGARUH PENGEMBANGAN SUMBERDAYA MANUSIA TERHADAP KINERJA PENGELOLA WISATA KOTA LUBUKLINGGAU - Muhammad Effendi; Agus Efriyansya (LPPM UNIVERSITAS BINA INSAN, 2017)
Lack of direct training processes, lack of rotation, lack of training in a learning class with a trainer, lack of simulation training, lack of training as tourism workers / managers play a role as visitors, lack of case studies, and lack of training involving mentoring in Lubuklinggau city attractions. Based on these problems, the objectives to be achieved through research is to determine the effect of human resource development on the performance of tourism managers in Lubuklinggau City. The research period was conducted for six months from November 2016 to April 2017. Techniques for collecting data with documentation, interviews and dissemination questionnaire. This research was carried out in tourist attractions in Lubukinggau City such as Nature Tourism including Sulap Resot Hill, Temam Waterfall which is housed in the Lubuklinggau City Culture and Tourism Agency. Using simple linear regression techniques, correlation coefficients and t test. The study uses SPSS 22, partial regression testing (t test) training on performance obtained df = (n-1) = 30-1 = 29 so that the value of ttable is 1.699 and the value of tcount = 4.538. Thus, the value of tcount (4,538)> t table (1,699) so that Ho is rejected and Ha is accepted. it means that there is the influence of the development of human resource training on the performance of tourism managers in Lubuklinggau city with a correlation coefficient of 0.651. From the results of the study, it should be from the side of the Lubuklinggau City Culture and Tourism Office to be able to develop the quality of tourism managers through training.